THE STUDY OF USING VIDEO LYRIC TO MOTIVATE STUDENTS IN LEARNING PASSIVE VOICE - Pebby Pixtilany Nur Saputri; Lilies Youlia Friatin; Luthfiyatun Thoyyibah (Universitas Galuh, 2021)
This study is aimed to investigate the effectiveness of using video lyric in learning passive voice toward students’ motivation and students’ perception on learning passive voice using video lyric. In collecting the data, the study used qualitative method especially case study; and triangulation method were observation, interview and questionnaire as instruments. This study was conducted at one of Senior High School in Majenang. Purposive sampling was used to select fifty three students as participants. The writer observed the activities in the classroom using naturalistic record and transcribed the conversation using notes. The writer used semi-structure interview and interpreting the answer of interviewee. The last, she gave twelve questions to the students followed by calculating the frequency and the percentage of each statement. The findings revealed that there were several steps used by teacher to give motivation in learning passive voice using video lyric: 1) giving some simulation; 2) asking students to watch some video of song; 3) asking students to sing a song together; 4) asking the students to write the lyric when the teacher explained the the passive voice; and 5) giving a treatment when the students deliver questions. Meanwhile, students perceived learning passive voice using video lyric positively. They joined with peer and other students; they also enjoyed and gave good attitude. Almost all of the students were enthusiastic when the teacher showed the video lyric. They assumed that video lyric was easier to comprehend passive voice in term of structure and formula. In addition, it improved their imagination, increased their critical thinking, creativity, and comprehension of learning experiences using new teaching aids. Using video lyric as teaching aids can help students to keep their interest in learning. It is very important for the teacher to increase their variety tools in learning activities. Keywords: Motivation, Passive voice, Video lyric.